2018
DOI: 10.1007/s11356-018-3099-3
|View full text |Cite
|
Sign up to set email alerts
|

Remediation of TCE-contaminated groundwater using KMnO4 oxidation: laboratory and field-scale studies

Abstract: The objectives of this study were to (1) conduct laboratory bench and column experiments to determine the oxidation kinetics and optimal operational parameters for trichloroethene (TCE)-contaminated groundwater remediation using potassium permanganate (KMnO) as oxidant and (2) to conduct a pilot-scale study to assess the efficiency of TCE remediation by KMnO oxidation. The controlling factors in laboratory studies included soil oxidant demand (SOD), molar ratios of KMnO to TCE, KMnO decay rate, and molar ratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 27 publications
1
4
0
Order By: Relevance
“…The present study focused on a CRBP system to measure the discharge of varied levels of KMnO 4 oxidant into aqueous systems. In the batch systems, dissolution of the PCL polymer releasing the KMnO 4 corresponded to what had been seen in other controlled-release systems [5] [23] [25] and, more specifically, with systems utilizing the same polymer oxidant system [20] [27]. As the amount of KMnO 4 in the PCL polymer pellets increased, a greater fraction of the oxidant was released as a function of time (Figure 2).…”
Section: Resultssupporting
confidence: 69%
See 2 more Smart Citations
“…The present study focused on a CRBP system to measure the discharge of varied levels of KMnO 4 oxidant into aqueous systems. In the batch systems, dissolution of the PCL polymer releasing the KMnO 4 corresponded to what had been seen in other controlled-release systems [5] [23] [25] and, more specifically, with systems utilizing the same polymer oxidant system [20] [27]. As the amount of KMnO 4 in the PCL polymer pellets increased, a greater fraction of the oxidant was released as a function of time (Figure 2).…”
Section: Resultssupporting
confidence: 69%
“…In situ chemical oxidation (ISCO) is one such remediation technology that has gained wide acceptance as a subsurface and groundwater treatment measure [1] [2] [3]. The purpose of chemical oxidation (or antioxidant) is to oxidize harmful chemicals in the environment to a less harmful level without inducing additional harm to surrounding areas and ecosystems or producing harmful by-products [4] [5]. ISCO oxidants generally include hydrogen peroxide, ozone, ferrate (VI), zero-valent iron and perhaps the most often used, permanganate [4] [6] [7] [8] [9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, for those not working in industries that risk exposure to TCE but are still continuously exposed to polluted underground water through dermal exposure, it is possible to indicate that the past use of underground polluted water has contributed to adverse renal effects among residents. Therefore, it is crucial to immediately remediate TCE-contaminated groundwater under environmentally-related conditions using the continuous supplement of high concentrations of KMnO4 [32] and biomimetic iron-nitrogen-doped carbon [33].…”
Section: Discussionmentioning
confidence: 99%
“…Potassium Permanganate (KMnO₄) has been widely used as a strong oxidant for the remediation of groundwater contaminated by chlorinated ethylenes such as trichloroethylene (TCE), perchloroethylene (PCE), Vinyl Chloride (VC), and dichloroethylene (DCE) [ [1] , [2] , [3] , [4] ] due to its relatively high stability, oxidation potential, diffusion in low permeability zones and cost-efficiency [ 5 ]. Studies have demonstrated that KMnO₄ can oxidize chlorinated ethylene compounds into both easily degradable and non-hazardous by-products such as hydrogen chloride, carbon dioxide, and organic acids through spontaneous cleavage of carbon-carbon bond [ 1 , [5] , [6] , [7] , [8] , [9] ].…”
Section: Introductionmentioning
confidence: 99%